Hoidon kohteesta tiedostavaksi asiakkaaksi: Tyytymättömyyden ilmaisun kielelliset keinot potilasasiavastaavalle osoitetuissa muistutuksissa - Paananen, Jenny; Sirkiä, Linda; Kangasniemi, Mari (Suomen Soveltavan Kielitieteen Yhdistys AFinLA ry, 2026)
• Hoidosta ja kohtelusta valittaminen on yleistynyt viimeisen vuosikymmenen aikana huomattavasti. • Potilasasiavastaavalle kirjoitetut muistutukset heijastavat potilaan asemaa tiedostavana ja oikeutensa tuntevana asiakkaana. • Tyytymättömyyttä ilmaistaan kuvaamalla ammattilaisten toiminnan odotuksenvastaisuutta ja siitä seurannutta kielteistä tunnekokemusta. • Tyytymättömyyden ilmauksia kärjistämällä voimistetaan muistutuksen kriittisyyttä ja affektiivisuutta.
In this article, we analyze how patients and their family members express dissatisfaction in complaints addressed to a patient ombudsman of a Finnish hospital. In the analysis, we focus on how dissatisfaction is expressed with the use of evaluative language. The data consist of 140 complaints, and the method of the study is qualitative text analysis. Expressing strong affects and judging the morality of professionals’ actions are characteristic to complaints. The writers of the complaints express their dissatisfaction by describing the unexpectedness of the professionals’ actions and conduct and the resulting negative customer experience. Unexpectedness is described, among other things, by using negation and extreme case formulations (kukaan ei koskaan soittanut ‘nobody ever called’) and expressions of astonishment (Miten tällaista voi tapahtua? ‘How can this happen?). Negative affect is often intensified (olin todella peloissani ‘I was really scared’). In addition, affectivity is strengthened by using capital letters and multiple punctuation marks.
AFinLAn vuosikirja: Kieli avaimena muuttuvaan maailmaan